Exercise is medicine… when you enjoy it: Exercise enjoyment, relapse prevention efficacy, and health outcomes for youth within a drug and alcohol treatment service. (January 2021) - Furzer, Bonnie; Rebar, Amanda; Dimmock, James A.; More, Alissa; Thornton, Ashleigh L.; Wright, Kemi; Colthart, Allan; Jackson, Ben
Abstract: Objective: Evidence for the effectiveness of exercise as therapy for youth substance use disorder (SUD) is scarce. In this study, we investigated associations between exercise enjoyment and recovery outcomes for youth undergoing residential SUD treatment. Method: Using ecological momentary assessment, each week participants reported perceptions of exercise enjoyment, relapse prevention efficacy, self-esteem, and physical health, and associations between these variables were assessed at both between- and within-person levels. There were 97 participants (age: M  = 17.5, SD = 1.57, range = 14 to 21; 37 female, 60 male), with a final sample of 64 due to participants ( n  = 33) discontinuing treatment within 2 weeks of commencement. Of the remaining sample, 50% ( n  = 32) completed 3 or more assessments, 40% ( n  = 26) completed 5 or more, and 25% ( n  = 16) completed 7 or more. Results: Relapse prevention efficacy, self-esteem, and perceived physical health increased over time in the program. Youth who, on average, enjoyed exercise more had higher self-esteem, perceived physical health, and relapse prevention efficacy than those who enjoyed it less. Additionally, on occasions when youth enjoyed exercise more (relative to their own average), they reported higher self-esteem, perceived physical health, and relapse prevention efficacy than on occasions when they reported enjoying it less. Conclusion: Participation in—and importantly, enjoyment of—exercise was linked to key health indices and predictors of relapse for youth during SUD treatment. These findings demonstrate that participation in enjoyable structured exercise may provide an important component of successful SUD treatment. Highlights: One of the first studies to identify within-person effects of exercise enjoyment for youth with substance use disorders. Positive between- and within-person effects for youth exercise enjoyment on recovery and general wellbeing outcomes. Exercise enjoyment was positively associated with self-esteem and perceived physical health. Youth who enjoyed exercise more had greater confidence to resist drug/alcohol use. Enjoyable exercise may be a valuable behavioral replacement strategy in youth addiction recovery.